New methodology to diagnose reliability of a single distribution circuit in Colombia (2017)
A reliable electric power supply is of ever increasing importance in the Colombian electricity market. As such, the Energy and Gas Regulation Commission, (CREG for its acronym in Spanish), has contracted technical studies to be undertaken in order to assess reliability for Colombian electric utilities. This paper focuses on a new methodology to diagnose the reliability of a single distribution circuit that is to be used in Colombian electric utilities. The proposed methodology includes calculating known reliability indexes (SAIFI, SAIDI, CAIDI, etc.) as well as new reliability indexes in order to determine the incidence of causes of failure. This paper explains some of the required files´ characteristics (input and output files) in order to execute two applications associated with the previously mentioned methodology. These two applications were developed using Microsoft Excel for the Strategic Energy Business Unit at EMCALI EICE ESP, located on Santiago de Cali, Valle del Cauca, Colombia, South America. This article describes some features of these applications. The first case study presented, about the first application, is calculated based on this methodology, and results obtained are compared with those obtained using ETAP software. Finally, the second case study, regarding the second application, is calculated based on this methodology and results obtained are shown in this document.